Functional dystonia and the borderland between neurology and psychiatry: New concepts. Issue 12 (18th October 2016) - Newby, Rachel; Alty, Jane; Kempster, Peter
ABSTRACT: Mind‐brain dualism has dominated historical commentary on dystonia, a dichotomous approach that has left our conceptual grasp of it stubbornly incomplete. This is particularly true of functional dystonia, most diagnostically challenging of all functional movement disorders, in which the question of inherent psychogenicity remains a focus of debate. Phenomenological signs considered in isolation lack the specificity to distinguish organic and nonorganic forms, and dystonia's variability has frustrated attempts to develop objective laboratory‐supported standards. Diagnostic criteria for functional dystonia that place emphasis on psychiatric symptoms perform poorly in studies of reliability, partly explained by the high frequency of psychopathology in organic dystonia. Novel approaches from the cognitive neurosciences may offer a way forward. Theory on Bayesian statistical prediction in cognitive processing is supported by sufficient experimental evidence for this model to be taken seriously as a way of reconciling contradictory notions about voluntary and unconscious motor control in functional movement disorders. In a Bayesian formulation of functional dystonia, misallocation of attention and abnormal predictive beliefs generate movements that are executed without a sense of agency. Building on this framework, there is a consensus that a biopsychosocial approach is required and that a unified philosophy of brain and mind is the best way to locate dystonia in the neurology‐psychiatry borderland. At a practical level, movement disorder neurologists are best placed to differentiate organic from functional dystonia. The main role of psychiatrists is in the diagnosis and management of the primarily psychiatric disorders that often accompany dystonia. © 2016 International Parkinson and Movement Disorder Society